Manifestasi hidden curriculum dalam pendidikan agama islam - Sabriadi HR (EKSPOSE, 2020)
The discussion in this paper is motivated by the ideality of the objectives of Islamic education which have been formulated formally in the curriculum sometimes are not in accordance with the reality that occurs in the learning process.  This is the caused by various factors that affect learning outcomes outside the curriculum formulation that has been planned.  The accumulation of various factors is called hidden curriculum. It exists as a side product of the of Islamic education that is not planned nor programmed in the formal curriculum.  Hidden curriculum of Islamic education is formulated through the the clear and strict regulation or policies that support the achievement of objectives, and are carried out routinely or continuously.  It is supported by structuring management of school organizations and harmonization of interactions between school members, as well as policies that support effective learning.Pembahasan dalam tulisan ini dilatar belakangi oleh idealitas tujuan pendidikan agama Islam yang telah dirumuskan dalam kurikulum secara formal terkadang tidak sesuai dengan kenyataan yang terjadi dalam proses pembelajaran. Hal ini Adanya berbagai faktor yang berpengaruh terhadap hasil pembelajaran di luar rumusan kurikulum yang telah direncanakan. Akumulasi dari berbagai faktor tersebut disebut hidden curriculum. Lahiir sebagai hasil sampingan praktek pendidikan agama Islam yang tidak direncanakan dan tidak deprogram dalam kurikulum secara formal. Hidden curriculum pendidikan agama Islam diformulasi melalui rumusan rules atau aturan yang jelas dan tegas, regulations atau kebijakan yang menunjang tercapainya tujuan, dan dijalankan secara routines atau kontinyu. Ditunjang dengan penataan manajemen organisasi sekolah dan harmonisasi intraksi antar warga sekolah, serta kebijakan yang menopang terlaksananya pembelajaran secara efektif.